1997
DOI: 10.1093/carcin/18.4.817
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analysis of buccal cells and lymphocytes from benzene-exposed workers

Abstract: Benzene is a well-characterized human carcinogen and clastogen still present in both the occupational and general environment. However, the levels of benzene encountered today are, in most cases, relatively low and new methods, more specific and sensitive than classical cytogenetics, are probably needed to assess if current benzene exposures pose a genotoxic risk to human health. Bearing in mind the leukaemogenic action of benzene, blood lymphocytes appear to be a suitable cell system for biomonitoring studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 12 publications
2
34
2
1
Order By: Relevance
“…The MN assay has been applied in studies of benzene exposure only during the last decade (Table 6) (Carere et al, 1995;Carere et al, 1998a;Gao et al, 1994;Högstedt et al, 1991;Holland et al, 1999;Liu et al, 1996;Nise et al, 1991;Surrallés et al, 1997;Xu et al, 1995;Zhang, 1996a). More than half of these studies found no association between increased MN frequency and exposure to benzene (Carere et al, 1995;Carere et al, 1998a;Högstedt et al, 1991;Holland et al, 1999;Nise et al, 1991;Surrallés et al, 1997), but almost all of these negative studies involved relatively low levels of exposure (< 5 ppm) (Carere et al, 1995;Carere et al, 1998a;Högstedt et al, 1991;Nise et al, 1991;Surrallés et al, 1997).…”
Section: Micronuclei (Mn)mentioning
confidence: 99%
See 2 more Smart Citations
“…The MN assay has been applied in studies of benzene exposure only during the last decade (Table 6) (Carere et al, 1995;Carere et al, 1998a;Gao et al, 1994;Högstedt et al, 1991;Holland et al, 1999;Liu et al, 1996;Nise et al, 1991;Surrallés et al, 1997;Xu et al, 1995;Zhang, 1996a). More than half of these studies found no association between increased MN frequency and exposure to benzene (Carere et al, 1995;Carere et al, 1998a;Högstedt et al, 1991;Holland et al, 1999;Nise et al, 1991;Surrallés et al, 1997), but almost all of these negative studies involved relatively low levels of exposure (< 5 ppm) (Carere et al, 1995;Carere et al, 1998a;Högstedt et al, 1991;Nise et al, 1991;Surrallés et al, 1997).…”
Section: Micronuclei (Mn)mentioning
confidence: 99%
“…More than half of these studies found no association between increased MN frequency and exposure to benzene (Carere et al, 1995;Carere et al, 1998a;Högstedt et al, 1991;Holland et al, 1999;Nise et al, 1991;Surrallés et al, 1997), but almost all of these negative studies involved relatively low levels of exposure (< 5 ppm) (Carere et al, 1995;Carere et al, 1998a;Högstedt et al, 1991;Nise et al, 1991;Surrallés et al, 1997). On the other hand, increased MN frequencies in pokeweed mitogen (PWM) stimulated lymphocytes of exposed workers were detected in two studies (Högstedt et al, 1991;Nise et al, 1991).…”
Section: Micronuclei (Mn)mentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of exposure were observed with PAHs (18,19), benzene (28), epichlorohydrin (40), pesticides (44), fluorides (47), cytostatics (50), and cosmic radiation (54). No effects were induced by VOCs (23,24), benzene (26,33), styrene (36), BD (37), malathion (46), or cosmic radiation (55).…”
Section: Discussionmentioning
confidence: 99%
“…The use of buccal mucosa cells (BMC) as study material offers a number of advantages, which include the following: (a) chemotherapeutic agents and radiation therapy limit the proliferative ability of the epithelium, producing thinning and ulceration manifested predominantly in gastrointestinal and oral mucosa (23); (b) the BMC lining serves as a mirror for health status, reflecting changes in the systemic conditions, such as oxidative stress (24), nutrient deficiency (25)(26)(27), or human exposure to genotoxins (28)(29)(30)(31); (c) 90% of all cancers arise from epithelial tissue (32) and the use of oral exfoliated cells is therefore considered a powerful diagnostic tool for monitoring genetic damage in human populations (33); (d) BMCs are directly exposed to xenobiotics in food and the environment, making them the most interesting cell type to explore different aspects of oxidative stress and carcinogenesis. The ease of harvest and biochemical analysis (34) of good quantity and quality DNA (35) makes them an excellent indicator cell for the extent of DNA damage that the epithelium may be experiencing.…”
Section: Introductionmentioning
confidence: 99%